Wood Vinegar as Plant Growth and Defense Inducer of Banana Plants against Ralstonia syzygii subsp. celebesensis - Nurrahmawan, Muhammad Evan; Giyanto; Nawangsih, Abdjad Asih; Sulistiani, Erina (Jurnal Fitopatologi Indonesia, 2022)
Wood Vinegar as Plant Growth and Defense Inducer of Banana Plants against Ralstonia syzygii subsp. celebesensisBanana seedlings derived from tissue culture are known to be susceptible to stress at early growing stage in the field. Pre-conditioning of seedlings using priming agents, such as coconut shell wood vinegar was reported to enhance plant growth and resistance. This study aimed to obtain information on the effect of coconut shell wood vinegar on growth and defense-related enzymes activity of Cavendish banana plantlet in the root induction phase and suppression of R. syzygii subsp. celebesensis in vitro. Research was conducted involving evaluation of wood vinegar phytotoxicity, analysis of plantlet growth, analysis of peroxidase and polyphenol oxidase activities, isolation of R. syzygii subsp. celebsensis, and toxicity assay of wood vinegar against R. syzygii subsp. celebesensis in vitro. Application of wood vinegar at 1.5% concentraion was phytotoxic, indicated by symptom development including chlorosis, necrosis, mucus secretion and plantlet death. Lower concentration of wood vinegar, i.e. ≤ 1.0% was not phytotoxic; even the treatment of wood vinegar at 0.1% caused an optimum increase in plantlet growth. Application of wood vinegar also increased the activity of defense-related enzymes at 2, 4, and 6 days after planting (DAP) but decreased at 30 DAP. Furthermore, wood vinegar showed antibacterial properties through the formation of inhibition zones and it caused decreased in the value of R. syzygii subsp. celebesensis cell densities. This study shows the potential of priming techniques for controlling banana blood disease, especially for banana seedlings propagated through tissue culture.